2006
DOI: 10.1038/sj.ki.5001514
|View full text |Cite
|
Sign up to set email alerts
|

Survival predictability of time-varying indicators of bone disease in maintenance hemodialysis patients

Abstract: Although renal osteodystrophy and vitamin D analogs may be related to survival in maintenance hemodialysis (MHD) patients, most studies have examined associations between baseline values and survival without accounting for variations in clinical and laboratory measures over time. We examined associations between survival and quarterly laboratory values and administered paricalcitol in a 2-year (July 2001-June 2003) cohort of 58,058 MHD patients from all DaVita dialysis clinics in USA using both time-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
790
9
23

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 834 publications
(870 citation statements)
references
References 44 publications
48
790
9
23
Order By: Relevance
“…A possible explanation for the described association between total serum ALP level and mortality is that ALP is a marker of high-turnover bone disease, which has been linked to higher mortality (15,16). However, ALP may be more than a marker of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the described association between total serum ALP level and mortality is that ALP is a marker of high-turnover bone disease, which has been linked to higher mortality (15,16). However, ALP may be more than a marker of bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined the association between ALP level and mortality in HD patients. Kalantar-Zadeh et al (15) showed a higher risk of all-cause mortality associated with higher baseline and time-varying ALP levels in HD patients using the DaVita database. However, these analyses were not adjusted for serum calcium and phosphorus levels, which have been associated with higher mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some inherent limitations in the USRDS dataset, in particular the lack of key pre-ESRD care data; hence, there is an urgent need for innovative linkage approaches to address this shortcoming. Similarly, whereas over the past decade some important contributions related to dialysis patient studies and outcomes have emerged as a result of epidemiologic analyses of large national dialysis databases in the USA such as those from the clinical care of Fresenius [36] and DaVita patients [37], these databases often lack pre-ESRD data. Hence, linking the pre-transition or prelude data to large national ESRD databases and analyzing the prelude variables as predictors of early ESRD outcomes enables better examination of the impact of pre-ESRD care on outcomes during the RRT.…”
Section: M I Tat I O N S O F T H E L a R G E N At I O N A L D I Amentioning
confidence: 99%
“…Whereas the traditional cardiovascular risk factors do not account for the increased mortality in CKD patients (3,4), measures of mineral and bone disorders (MBD), including hyperphosphatemia, are associated with increased death risk (5)(6)(7)(8)(9). Hyperphosphatemia may be involved in the pathogenesis of vascular calcification (10)(11)(12).…”
mentioning
confidence: 99%